The scope for trade restrictions to address the lack of compliance with fire safety standards in garment factories of Bangladesh - Islam, Md. Rizwanul; Muquim, Naimul (© 2015 Kluwer Law International BV, The Netherlands., 2016)
This article was published in the Journal of World Trade [© 2015, Kluwer Law International BV, The Netherlands] and The Journal's website is at: https://www.kluwerlawonline.com/abstract.php?area=Journals&id=TRAD2015006